The Associations of rs1799724 and rs361525 With the Risk of Ankylosing Spondylitis Are Dependent on HLA-B27 Status in a Chinese Han Population - Sheng, Nan; Gao, Yingying; Li, Hui; Wang, Wenwen; Geng, Linyu; Zhang, Bo; Huang, Qiang; Wang, Xueqin; Sun, Lingyun (Frontiers in Immunology, 2022)
Objectives: Human leucocyte antigen B27 (HLA-B27) is an important biomarker for ankylosing spondylitis (AS). However, delay in the diagnosis of AS is still common in clinical practice. Several single nucleotide polymorphisms (SNPs) in the coding gene of tumor necrosis factor alpha (TNFα) have been reported to be AS susceptibility loci. Our aim was to explore whether SNPs in TNFα could be used to improve the performance of HLA-B27 for predicting AS. Methods: Five SNPs (rs1799964, rs1800630, rs1799724, rs1800629 and rs361525) spanning TNFα were genotyped by qPCR-Invader assay in 93 AS patients and 107 healthy controls for association analysis and linkage disequilibrium (LD) analysis. Random forest algorithm was utilized to construct the predictive classifiers for AS. HLA-B was genotyped by PCR-sequence-based typing in a subset of the HLA-B27 positive subjects (38 AS patients and 5 healthy controls). Results: The T allele of rs1799724 was verified to significantly increase the risk of AS (OR = 4.583, P < 0.0001), while the A allele of rs361525 showed an association with the reduced AS risk (OR = 0.168, P = 0.009). In addition, the rs1799964T-rs1800630C-rs1799724T-rs1800629G-rs361525G haplotype was significantly associated with a higher risk of AS (P < 0.0001). The optimal set of variables for classifiers to predict AS only consisted of HLA-B27. Strong associations with HLA-B27 status were found both in rs1799724 (P < 0.0001) and rs361525 (P = 0.001), and all the analyzed HLA-B27 positive subjects carried HLA-B*27:04 or HLA-B*27:05. Conclusion: In the Chinese Han population, the minor allele T of rs1799724 could increase the risk of AS, while the minor allele A of rs361525 protect individuals from AS. However, the contributions of rs1799724 and rs361525 to AS risk were dependent on HLA-B27 status, suggesting the importance of taking the independence and specificity into consideration in AS susceptibility loci studies.